Teachers' Experiences on Gender Issues - Daniel Rubén Tacca Huamán; Barbara Carletti; Renzo Cuarez Cordero; Ana Luisa Tacca Huamán; Miguel Angel Alva Rodriguez; Luis Junior Tirado Castro (University of Bologna, 2024)
Gender issues are still under debate in Latin American societies, especially in the educational sphere; for this reason, the objective of the research was to know the experiences of high school teachers regarding gender issues in the classroom and during their university education. The research was qualitative, phenomenological and 22 teachers participated voluntarily. Unanimity was not found in the use of terms related to gender; most of the participants have been adapting their didactic strategies to give the same opportunities to all their students; in addition, the role of the family in the formation of adolescents and in the construction of stereotypes is recognized. Finally, a lack in gender issues was evidenced in the educational proposal of teacher training centers. According to the above, there is still a long way to go in terms of gender issues in education and teacher training.